Secondary Thermoplastic Modified Wood-Polymer Composite with Increased Technological, Mechanical and Dielectric Properties - Kopylov, Serhii; Cherkashina Аnna; Bliznyuk, Oleksandr; Gorbunov, Kostiantyn; Petrov, Serhii; Filenko, Olesya; Makhonin, Mykola; Tsereniuk, Oleksandr (Journal of Research Updates in Polymer Science, 2024)
The article describes the development of new formulations of wood-polymer composites with a modified polymer matrix and the study of their technological, mechanical and dielectric properties. The research aim is to create a new composition of wood-polymer composites based on secondary raw materials with an improved set of technological, mechanical and dielectric properties, namely, the modification of the polymer matrix and the development of a new technology for its production. The optimal composition of the polymer matrix and modification influence of the wood-polymer composites polymer matrix on the physical, mechanical and dielectric properties of the samples are determined. Strength, impact resistance, abrasion, mechanical and dielectric properties are studied. A description of the climatic influences on the wood-polymer composites including the influence of moisture and temperature is given.